Storage Management for Algol68 - Birrell, Andrew (ACM SIGPLAN Notices, 1977)
This paper describes some of the techniques which can be used for managing the run time storage required for an ALGOL68 program. The emphasis is on stack storage, since garbage collection techniques would require another paper. The Frcblems caused by some ALGOL68 constructs are described: the solutions given are mainly those adopted in the Cambridge ALGOL68C system.